1999
DOI: 10.1021/jp990787j
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir Films of Amphiphilic Crown Ethers

Abstract: We have used X-ray reflectivity and grazing-incidence X-ray diffraction to study amphiphilic crown ethers 1 and 2 at the air-water interface. A new synthetic route was employed, which substantially reduced the level of impurities. Unlike previous studies of 1, we saw no evidence of a first-order lying-down to standingup transition of the alkyl tails. We did observe in both compounds a gradual reorientation of the tails away from the interface as the film was compressed, followed by an irreversible collapse to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These surfactants are multifunctional ones with selective cationinclusion ability. Although there are some reports on insoluble monolayers of various crown ether surfactants having a hexadecyl or longer hydrocarbon tail [1][2][3][4], many studies on water-soluble crown ether surfactants have been reported by Le Moigne et al [5,6], Moroi et al [7], Kuwamura et al [8][9][10][11], Okahara et al [12][13][14] and Ozeki et al [15][16][17][18][19][20][21][22]. Summarizing these reports, crown ether surfactants are less hydrophilic than linear polyoxyethylene surfactants, so 18-crown-6 compounds with a decyl or longer alkyl tail cannot dissolve in water but can dissolve in aqueous solutions of metal salts because of an increase in hydrophilicity due to the formation of crown ether surfactant/metal cation complex.…”
Section: Introductionmentioning
confidence: 99%
“…These surfactants are multifunctional ones with selective cationinclusion ability. Although there are some reports on insoluble monolayers of various crown ether surfactants having a hexadecyl or longer hydrocarbon tail [1][2][3][4], many studies on water-soluble crown ether surfactants have been reported by Le Moigne et al [5,6], Moroi et al [7], Kuwamura et al [8][9][10][11], Okahara et al [12][13][14] and Ozeki et al [15][16][17][18][19][20][21][22]. Summarizing these reports, crown ether surfactants are less hydrophilic than linear polyoxyethylene surfactants, so 18-crown-6 compounds with a decyl or longer alkyl tail cannot dissolve in water but can dissolve in aqueous solutions of metal salts because of an increase in hydrophilicity due to the formation of crown ether surfactant/metal cation complex.…”
Section: Introductionmentioning
confidence: 99%
“…Air/water interface provided a crucial environment for different molecules to react with each other, and many supramolecular assemblies were fabricated through the interaction at the air/water interface. [14][15][16][17] In addition, a lot of systems showing molecular recognition properties, such as crown ether [18][19][20] and calixarene, [21][22][23][24] have been widely investigated. Molecular recognition through hydrogen bonding is one of the most attractive topics in supramolecular systems, and excellent work has been done by Ariga, Kunitake, et al at the air/water interface.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl 3,4-di(hydroxyl)benzoate (2) 52 and 4-hydroxybenzoic acid tert-butylester (11) were prepared as reported in the literature. 53 Methyl 3,4-di(decyloxy)benzoate (3, yield 91%), methyl 3,4-di(dodecyloxy)benzoate (4, 89%), methyl 3,4-di (hexadecyloxy)benzoate (5, 74%), 3,4-di(decyloxy)benzoic acid (7, 96%), 3,4-di(dodecyloxy)benzoic acid (8, 85%), 3,4-di(hexadecyloxy)benzoic acid (9, 100%), 4-[3,4-di(decyloxy)benzoyloxy] benzoate (13, 67%), 4-[3,4-di(hexadecyloxy)benzoyloxy] benzoate (14, 68%), 4-[3,4-di(decyloxy)benzoyloxy] benzoic acid (17, 100%), and 4-[3,4-di(hexadecyloxy)benzoyloxy] benzoic acid (19, 100%) were synthesised according to Goodby et al 36 and characterized by NMR spectroscopy. The similar tricatenar derivatives (see Scheme 3) 27 (71%), 28 (90%), 29 (71%) and 30 (99%) were obtained by following the same protocols.…”
Section: Synthesis and Characterisationsmentioning
confidence: 99%
“…4-[3,4-Di(dodecyloxy)benzoyloxy] benzoic acid (18). Following a modified procedure, 53 a solution of ester 15 (167 mg, 0.25 mmol) in dichloromethane (10 cm 3 ) was cooled to 0 1C. Anisole (1 cm 3 ) followed by trifluoroacetic acid (2.5 cm 3 ) were added and the mixture stirred at 0 1C for 3 h and then 1 h at room temperature.…”
Section: Synthesis and Characterisationsmentioning
confidence: 99%